DIFFERENTIALLY REGULATED GENES IN THE SALIVARY GLANDS OF BROWN PLANTHOPPER AFTER FEEDING IN RESISTANT VERSUS SUSCEPTIBLE RICE VARIETIES. Issue 2 (22nd January 2015) - Wang, Xiaolan; Zhang, Mei; Feng, Fei; He, Ruifeng
<x xml:space="preserve">Abstract</x> Brown planthopper (BPH) is a damaging insect pest of rice. We used suppression subtractive hybridization (SSH) and mirror orientation selection to identify differentially regulated genes in salivary glands of BPH after feeding on resistant and susceptible varieties. The forward SSH library included 768 clones with insertions ranging from 250 to 1000 bp. After differential screening, a total of 112 transcripts were identified, which included 27 upregulated genes and seven downregulated genes. Several of these transcripts showed sequence homology to known proteins such as trehalase, mucin‐like protein, vitellogenin, calcium ion binding protein, and eukaryotic initiation factor‐like protein. About half of the transcripts, however, did not match to any sequences in the protein databases currently available. Functional annotation of the transcripts showed gene ontology association with metabolism, signal transduction, and regulatory responses. Notably, many known functional genes were predicted to be secreted proteins. Also, gene expression profiles of the salivary glands of BPH feeding on resistant rice (B5) and susceptible rice (TN1) varieties were compared. Our data provide a molecular resource for future functional studies on salivary glands and will be useful for elucidating the molecular mechanisms between BPH feeding and rice varieties with BPH resistance differences.